Efforts to Socialize the Food Security Program Through Islamic Boarding School Activities in Jambenenggan Village - Yepi Sopian; Siti Fauziah; Siti Anisa Yuniar; Siti Nurlaela; Agitsni Ginayah Roudhotul Jannah; Astri Nurafifah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service is the practice of science, technology for the community through scientific methodology as the noble responsibility of higher education institutions in an effort to develop community capabilities so that they can accelerate the achievement of national development goals (Congratulations, 1986). This service is carried out to fill activities in the month of Ramadan. One of these activities was in the form of a flash boarding school where the activity was carried out at three elementary schools around Jambenenggang Village. By holding this sanlat, we hope that students will be able to strengthen their understanding of the Islamic religion and how students can strengthen food security through reducing food wastage. The implementation was carried out for six days. We conducted an evaluation based on the results of interviews with participants that they were very enthusiastic about participating in the sanlat activity